Utilization of Terrarium Media in Science Learning to Improve Understanding Ecosystem and Students' Environmental Awareness - Khairul Amri; Fitri Adifa (Siber Journal of Advanced Multidisciplinary, 2026)
This research is motivated by the low cognitive learning outcomes and environmental awareness among students due to ecosystem topics traditionally being delivered in an abstract and theoretical manner. This study, entitled "Pemanfaatan Media Terrarium dalam Pembelajaran Ilmu Pengetahuan Alam untuk Meningkatkan Pemahaman Ekosistem dan Kesadaran Lingkungan Siswa," aims to examine the implementation of the project-based learning model utilizing terrarium media to improve students' cognitive achievement and environmental awareness. The method employed is classroom action research based on the Kemmis and McTaggart model, conducted over two cycles. The results demonstrate an increase in the average cognitive score from 52.25 to 84.50, with the final classical completeness reaching 91.30 percent and a Normalized Gain (N-Gain) value categorized as moderate. Meanwhile, the average score for students' environmental awareness rose from 50.73 percent to 82.21 percent, meeting the criteria for "highly conscious". In conclusion, the implementation of the project-based learning model with terrarium media is proven effective in significantly increasing cognitive learning success while simultaneously fostering students' environmental awareness.